Fire in Semi-Arid Shrublands and Woodlands: Spatial and Temporal Patterns in an Australian Landscape - van Etten, Eddie J. B.; Davis, Robert A.; Doherty, Tim S. (Frontiers in Ecology and Evolution, 2021)
Semi-arid landscapes are of interest to fire ecologists because they are generally located in the climatic transition zone between arid lands (where fires tend to be rare due to lack of fuel, but are enhanced following large rainfall episodes) and more mesic regions (where fire activity tends to be enhanced following severe rainfall deficits). Here we report on the characteristics of the contemporary fire regimes operating in a semi-arid region of inland south-western Australia with rainfall averaging around 300 mm per annum. To characterize fire regimes, we analyzed a geodatabase of fire scars (1960–2018) to derive fire preferences for each major vegetation type and fire episode and used known fire intervals to model fire hazard over time and calculate typical fire frequencies. We also used super epoch analysis and correlations to explore relationships between annual fire extent and rainfall received before the fire. We found fires strongly favored sandplain shrublands, and these tended to experience hot crown fires once every 100 years (median fire interval), with fire hazard increasing linearly over time. In contrast, fires were rare in eucalypt woodland and other vegetation types, with a median interval of 870 years and broadly consistent fire hazard over time. Annual fire extent was most strongly linked with high rainfall in the year prior to fire, and this was particularly so for eucalypt woodlands. Large-scale fires in shrublands tended to favor areas burnt in previous large fires, whereas in woodlands they favored edges. In conclusion, we found divergent fire regimes across the major vegetation types of the region. Sandplain shrublands were similar to Mediterranean shrublands in that they experienced intense stand-replacing wildfires which recovered vigorously although slowly, meaning burnt shrublands did not experience fires again for at least 25 and 100 years on average. In contrast, eucalypt woodlands were fire sensitive (trees readily killed by fire) and experienced fires mostly around the edges, spreading into core areas only after large rainfall events elevated fuel levels. Overall, both vegetation types subscribed to typical arid-zone fire regimes where elevated rainfall, and not drought, promoted fires, although the role of fuel accumulation over time was more important in the shrublands.